Analysis Of Protein Concentracion In Moringa Fruit (Moringa Oleifera) With Spektrofotometer Uv-Vis Mhetod - Ardiansah Hasin; Ida Wahyuni (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2020)
Research has been conducted on the analysis of protein levels in Moringa fruit by spectrophotometer UV-Vis. This type of research is a laboratory observation research that aims to analyze protein levels in Moringa Fruit. Benifits of this research are as an information material for the community about Moringa fruit and the importance of protein levels for the body. The examination method using Spektrofotometer UV-Vis on 3 samples of Moringa fruit with a wavelengthat of 550 nm obtained results is in the samples A= 2.614 mg/50g, samples B= 2.4883 mg/50g, and samples C= 2.7477 mg/50g. Recommended by consumers to consume Moringa fruit because it can meet protein needs in the body